Implikasi Perjanjian Perdagangan Bebas Terhadap Prinsip-Prinsip Hukum Perdata Internasional: Analisis Mendalam Tentang Pada Pemberlakuan Penyelesaian Sengketa Internasional - Rizky Satria Dimlana; Laila Yuniar Irsan; Muhamad Fadly Darmawan; M. Naufal Raihan Sukmana; Mustika Mega Wijaya (Universitas Sains dan Teknologi Komputer, 2024)
International Civil Agreements are legal relationships designed to facilitate support, business, or trade among the involved parties. These agreements entail elements of foreign involvement. The World Trade Organization (WTO) plays a pivotal role in expanding international trade and safeguarding the interests of its member countries, particularly developing nations. The WTO holds significant responsibility in overseeing and facilitating international trade to promote economic development and poverty reduction. Principles in resolving international trade disputes include: Principle of agreement among parties, freedom to choose dispute resolution methods, choice of law, good faith, and the principle of exhaustion of local remedies. The identified problem formulation revolves around how the application of international civil law influences free trade agreements in resolving international disputes and the efforts made in handling free trade disputes through international legal resolution. This study incorporates the theories of Lex loci solutionis, the proper law of contract, legal protection theory, and international agreement theory. The research adopts a normative approach involving the examination and analysis of applicable legal regulations. The application of international civil law here is highly complex and crucial to resolving potential disputes within the context of free trade agreements. Resolving international disputes through international civil law can support fair and regulated free trade while fostering cooperation among nations and relevant parties, employing principles and theories of international civil law such as lex loci solutionis and the proper law of contract. This approach significantly aids in resolving international disputes within free trade agreements. Utilizing international dispute resolution mechanisms like GATT and WTO, as well as bilateral and multilateral agreements, stands as a critical step in safeguarding free trade and promoting equitable rules in international trade. In situations involving trade disputes, efforts toward resolution must encompass both judicial and non-judicial avenues. Non-judicial avenues involve more flexible diplomatic methods such as negotiation, consultation, mediation, and arbitration. Judicial avenues are formal and binding, involving courts or tribunals in dispute resolution. These efforts represent positive strides towards achieving sustainable goals in free trade.